[Six attendees of the Black Frats in Umoja event] (1988)
The attendees are posing in front of a sorority or fraternity booth. Three of the participants are wearing white shirts (one of which has the words 'Dove Life' printed on it). Two others are wearing black, one with a pink undershirt and the other wearing solid black. The last participant in the group is wearing yellow. There are other participants at the event around them.